Human Resource Capacity And The Demands Of Decentralization Process In The Gambia - Modou Jonga (POLITICO, 2019)
This paper attempt to explore the documented challenges that constrain human resource development (HRD) under decentralization process in Local Government Authorities (LGAs) in The Gambia. Critical review on the demands of decentralization and human Resources Capacity gap was thoroughly done to set the basis for the paper. The Paper used documentary sources to gather information relevant to the thematic area. These included journal articles, books, Government Reports and Local Government Service Regulations. Observation method was also used based on the author’s background and experience in the thematic area. The paper found that decentralization as a process and as an approach has limited potential that enhance development of Human Resource Capacity in the Local Government Authorities in The Gambia. However the paper noted three major challenges which are multi-faceted and integrated in character. They comprise policy induced challenges, skills and Organization challenges and performance induced challenges. Hence the paper strongly recommends on institutional review and re-design the institutionalization of HRD, conduct a robust capacity assessment in all the Local Councils to measure their capacity and readiness to meet the demands of the decentralizationprocess. Enforcement mechanisms with financial support, change of mind set and working culture and finally political and leadership will remain critical for bridging the existing Human Resource capacity gaps to meet the demands of decentralization within the Local Government sector.